The Abundance of Toxic Dinoflagellate Gambierdiscus sp, Ostereopsis sp and Prorocentrum sp on Seagrass Leaf Thalassia sp from the Nirwana Beach West Sumatera Province - Rawati Irmaida Sitorus; Thamrin '; Syafruddin Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Dinoflagellate is a group of monocelullar microalga prossesing of double flagel. This organism can be found in a subtropic and also in a tropic marine water. Some potentially toxic epibentic dinoflagellate assemblage with macroalgae and potentially to cause blooming such as Gambierdiscus sp, Ostereopsis sp and Prorocentrum sp. Blooming of this population can generate